2014
DOI: 10.4414/smw.2014.14073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision support systems

Abstract: Clinical decision support (CDS) systems link patient data with an electronic knowledge base in order to improve decision-making and computerised physician order entry (CPOE) is a requirement to set up electronic CDS. The medical informatics literature suggests categorising CDS tools into medication dosing support, order facilitators, point-of-care alerts and reminders, relevant information display, expert systems and workflow support. To date, CDS has particularly been recognised for improving processes. CDS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 64 publications
0
80
0
3
Order By: Relevance
“…This implies that a hospital‐wide automated algorithm, which uses QTcB for assessment of a possible dangerous QT prolongation, would generate double the amount of alerts compared to an algorithm using the optimal QT correction formula. This could lead to alert fatigue and avoiding clinically indicated first‐choice drugs because of potential QT‐prolonging effects . Hence, using an optimal QT correction formula could reduce the workload and improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that a hospital‐wide automated algorithm, which uses QTcB for assessment of a possible dangerous QT prolongation, would generate double the amount of alerts compared to an algorithm using the optimal QT correction formula. This could lead to alert fatigue and avoiding clinically indicated first‐choice drugs because of potential QT‐prolonging effects . Hence, using an optimal QT correction formula could reduce the workload and improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the potential efficacy of alerts in the hospital setting (14)(15)(16); however, extensive reviews of the clinical decision support literature have consistently described specific elements that increase provider adherence and thus, the likelihood of alert success (17)(18)(19)(20). These factors include the speed of the information system, timing of the alert (real time and at the point of care), minimal disruption of and integration into provider workflow, simplicity and clarity of the message, and provision of references and sufficient information within the alert.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Alert fatigue is more likely when endogenous recognition and exogenous recognition are in conflict (i.e., an alert occurs for a condition of which a provider is already aware). Additionally, alert fatigue can occur due simply to the proliferation of alerts, even if they are informative (20,29,30). This is well documented in the intensive care unit, where frequent chimes, buzzers, and beeping fade quickly into background obscurity.…”
Section: Potential Harms Of Alertingmentioning
confidence: 99%
“…Generally, CDSS are designated to assist physicians or other health professionals during clinical decision-making. CDSS are demanded to be integrated into the clinical workflow and to provide decision support at time and location of care [1]. Data-driven CDSS, in particular, make use of data-mining and machine-learning techniques to extract and combine relevant information from patient data, in order to provide assistance for diagnosis and treatment decisions or even to be used in clinical quality control based on large-scale data [1].…”
Section: Introductionmentioning
confidence: 99%